2014
DOI: 10.1093/jac/dku431
|View full text |Cite
|
Sign up to set email alerts
|

Time-kill kinetics of antibiotics active against rapidly growing mycobacteria

Abstract: The total effect observed for all antibiotics was low and primarily determined by the Emax and not by the Hill's slope. The limited activity detected fits well with the poor outcome of antibiotic treatment for disease caused by RGM, particularly for M. abscessus. An evaluation of drug combinations will be the next step in understanding and improving current treatment standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 16 publications
6
56
0
Order By: Relevance
“…This is in line with our previous studies (10,16) as well as with another recent study assessing the activities of several antibacterial drugs against Mycobacterium abscessus (17). The results of our in vitro study underline the need for potentiation of clarithromycin activity against M. avium.…”
supporting
confidence: 92%
“…This is in line with our previous studies (10,16) as well as with another recent study assessing the activities of several antibacterial drugs against Mycobacterium abscessus (17). The results of our in vitro study underline the need for potentiation of clarithromycin activity against M. avium.…”
supporting
confidence: 92%
“…16,23,25 In addition, it exhibits more effective bacterial killing after 24 h relative to clarithromycin and cefoxitin. 36 However, the range of MICs of MABSC to amikacin varies widely, and a recent pharmacokinetic/pharmacodynamic model suggested that the current standard amikacin dose does not achieve the target C max /MIC ratio for M. abscessus for more than 75% of patients. 37 Therefore, the bactericidal activity against MABSC of current dosing ranges for amikacin has been questioned.…”
Section: Amikacinmentioning
confidence: 99%
“…Single exposures of amikacin and clarithromycin were previously described for both M. abscessus (16) and M. avium (17).…”
Section: Susceptibilitymentioning
confidence: 99%